Development, delivery, and evaluation of the Texas Epidemic Public Health Institute infection control module program 200 series - Kayla E. Ruch; Kayla E. Ruch; Anabel Rodríguez; Anabel Rodríguez; Janelle Rios (Frontiers in Public Health, 2025)
BackgroundThe Texas Epidemic Public Health Institute (TEPHI) aims to safeguard public health and the Texas economy by preparing for infectious disease outbreaks. The Infection Prevention and Control (IPC) Webinar series was created to offer free educational resources and continuing education for public health and healthcare personnel responsible for IPC programs in rural regions of Texas. The IPC 200 Series succeeds the founding IPC 100 Series established by the TEPHI Small Rural Healthcare Preparedness.MethodsIPC registration and attendance data were collected through WebEx® and Microsoft Teams®, which also served as the platforms for module delivery. Learning assessments and post-module evaluation surveys were administered using QuestionPro®. Module content was developed using resources adapted from the Association for Professionals in Infection Control and Epidemiology (APIC), the Occupational Safety and Health Administration (OSHA), the Centers for Disease Control and Prevention (CDC), The Joint Commission (TJC), and the Centers for Medicare and Medicaid Services (CMS). The Kirkpatrick Model assessed knowledge effectiveness through knowledge activities, post-evaluations, and a completion impact survey.ResultsIPC 200 Series had 1,088 attendees to live modules and generated >4,400 YouTube views. Each module was accredited for 1.0 hour of public health education and IPC certification (a-IPC), with eight of ten sessions offering 1.0 continuing education hours for certification in infection control (CIC) for infection preventionists. Of 286 participants completing post-knowledge assessments, the average score was 91.0% (Range: 81.0–96.0%). Post-evaluations (n = 271) rated the content highly (mean: 4.8/5.0) for beneficial, easy to understand, and clear/concise. Additionally, 90.4% of respondents indicated plans to implement the knowledge gained, and 98.9% expressed interest in attending future sessions.ConclusionIPC series improved participants’ knowledge of infection prevention and control best practices. By disseminating evidence-based education and providing no-cost continuing education, the series equipped healthcare personnel with the tools to foster safer environments for patients and staff in healthcare settings.